A Narrative Review of Performance and Health Research in US Army Rangers. Issue 5 (May 2023) - Roberts, Brandon M.; Mantua, Janna; Naylor, Jacob A.; Ritland, Bradley M.
Abstract: Roberts, BM, Mantua, J, Naylor, JA, and Ritland, BM. A narrative review of performance and health research in US army rangers. J Strength Cond Res 37(5): 1157–1161, 2023—The 75th Ranger Regiment (75RR) is an elite airborne infantry unit that is prepared to deploy on short notice and is resourced to maintain exceptional proficiency and readiness through prolonged deployments. Soldiers must be airborne qualified and pass a number of physical and psychological tests during training to become a member of 75RR. Rangers must maintain a level of physical performance comparable to high-level athletes while also handling operational stressors that include a negative-energy balance, high-energy expenditure, sleep restriction, and completing missions in extreme environments, all of which increase their chance of illness or infection. There are also situations of heighted injury risk, such as parachuting and repelling, which are routinely required in combat operations. Thus far, only one screening tool to assess injury risk has been developed. There are also physical training programs to enhance performance for Rangers in 75RR. This narrative review aims to evaluate the body of literature surrounding performance and health-related research in US Army Rangers to understand how Rangers are impacted during training or operations, to inform future training recommendations, and to identify areas of future research that are warranted and could potentially optimize the health and performance of Rangers during future training or operation events.